Hubungan Kelimpahan Fitoplankton Dengan Kandungan Nitrat dan Fosfat Pada Tambak Secure Di Kampung Suaran, Kabupaten Berau - Sigalingging, Andi; Bulan, Dewi Embong; Suryana, Irma (Jurusan Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, 2023)
Kampung Suaran Pond is one of the areas that will implement the SECURE pond concept. This pond concept can help increase pond productivity in a sustainable manner. Increased productivity in ponds is highly dependent on phytoplankton abundance and water quality. The purpose of this study was to determine the abundance of phytoplankton before becoming a secure pond and the relationship of phytoplankton abundance with nitrate and phosphate content. This research was conducted from January to May 2023. The sampling method was based on purposive sampling, adjusting the representative pond category according to the SECURE program monitoring. The results showed the abundance of phytoplankton in surface and bottom waters averaged 280 ind/L–760 ind/L. The number of phytoplankton identified consisted of 17 species and 3 classes, namely Bacillariophyceae (76,5%), Cyanophyceae (5,9%), and Dinophyceae (17,6%). The lowest nitrate concentration was found at point II at 0.066 mg/L and the highest at point I at 0,641 mg/L. The lowest phosphate concentration was at point II of 0,120 mg/L, and the highest was at point I of 0,438 mg/L. In ponds in Suaran village, there is a relationship between phytoplankton abundance with nitrate (r = 0,817) and phosphate (r = 0,893) in the surface and bottom waters of the pond, which shows a strong relationship.